The Effectiveness of Implicit Brand Placement in Online Videogame Streaming Services: An Eye Tracking Study - Duhaime, Vincent; Prom Tep, Sandrine; Arcand, Manon (Journal of Marketing Development and Competitiveness, 2020)
Widely studied in traditional advertising contexts, research on brand placement is still scarce on videogame streaming platforms such as Twitch. These environments combining video games and social media, this article investigates the impact of product placement on branding using eye tracking. Similar to Twitch content, a video was made of a professional gamer’s streaming session with Hearthstone. The video was randomly presented with or without product placement to 40 subjects, followed by a questionnaire. The results demonstrate that, it captures the attention of viewers, which positively affects unaided and aided brand recall, and that both positively influence attitude towards the brand.